Respuesta :

Answer:

Option D is correct.

Step-by-step explanation:

f(x)= 9x^2 -12

Let y = 9x^2 - 12

Switch places of x and y and solve for y

x = 9y^2 - 12

Adding 12 on both sides

x + 12 = 9y^2

Dividing both sides by 9

x+12/9 = y^2

=> Taking square root on both sides

=> [tex]\sqrt{y^2}= \sqrt{\frac{x+12}{9}}\\y=\pm\frac{\sqrt{x+12}}{3}[/tex]

Replace y with g(x)

[tex]g(x)=\pm\frac{\sqrt{x+12}}{3}[/tex]

Option D is correct.

Answer: Option D

[tex]g(x)=\±\frac{\sqrt{x+12}}{3}[/tex]  for [tex]x\geq -12[/tex]

Step-by-step explanation:

We have the following function

[tex]f(x) = 9x^2-12[/tex]

make [tex]f (x) = y[/tex]

[tex]y = 9x^2-12[/tex]

To find the inverse of the function, solve for the variable x

[tex]y+12 = 9x^2[/tex]

[tex]x^2=\frac{y+12}{9}[/tex]

[tex]x=\±\sqrt{\frac{y+12}{9}}[/tex]

[tex]x=\±\frac{\sqrt{y+12}}{3}[/tex]

Now interchange the variable x with the variable y

[tex]y=\±\frac{\sqrt{x+12}}{3}[/tex]  for [tex]x\geq -12[/tex]

Finally, make g(x) = y

[tex]g(x)=\±\frac{\sqrt{x+12}}{3}[/tex]  for [tex]x\geq -12[/tex]

ACCESS MORE